STRATEGI PEMASARAN PRODUK “LORJUK’ PADA INDUSTRI RUMAH TANGGA DI PAMEKASAN - Endang Triwahyurini (Universitas Islam Madura, 2015)
This study aims to determine the marketing mix strategy, and to learn about the market prospects of “lorjuk” made by home industries.The types of research used in this study was descriptive, which using survey technique, which specify the location of the research on intentional (purposive). Research conducted at several home industries located in the city of Pamekasan, with the consideration that in the area are small-scale shredded fish processing industry. The technique of determining the samples are using census methodology in which conducted on the entire study population, where the determination of samples considering certain criteria that have been made to the object in accordance with the purpose of research which is then processed using descriptive analysis. The study found some concept of marketing mix variables that implemented by shredded fish companies that include product marketing mix, price marketing mix, distribution marketing mix and promotion marketing mix which is used by the company's as a marketing strategy in competing with other companies that have similar product. The analysis found that the marketing mix strategy applied is efficient and prospective.